Design and Implementation Independent Battery and Lost-Link Fail-Safe Module for USV Safety - Setyawan Ajie Sukarno; Hisyam Nuruliman; Ridwan (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
This study presents the design and implementation of an independent battery and lost-link fail-safe module to improve the navigational safety and operational reliability of Unmanned Surface Vehicles (USVs). Previous studies on USV fail-safe systems mainly focused on battery monitoring or communication recovery separately and generally relied on the main onboard controller or autopilot system. Such approaches may reduce system reliability when the primary controller experiences malfunction or communication interruption. To address this limitation, the proposed system integrates a Jetson Orin Nano, a CUAV autopilot, and an independent ESP32-based monitoring module capable of autonomously monitoring battery and communication conditions. Communication reliability is evaluated using MAVLink heartbeat signals, while battery condition is assessed using a progress-based energy estimation method to predict mission feasibility according to the remaining battery capacity and mission progress. When abnormal conditions such as low battery or communication loss are detected, the system autonomously activates fail-safe actions, including return-to-home and loiter modes, to prevent mission failure and vehicle loss. Experimental results show that the proposed system achieves a voltage measurement accuracy of 99.87%. In addition, the fail-safe mechanism successfully detects low battery conditions within 2.5–3.0 seconds and communication loss within 6–15 seconds, demonstrating improved USV operational safety and reliability.